Research on the teaching mode of industrial design in local universities in China: from the perspective of professional ability appreciation - Han-you Wang; Qin-tao Pan; Xing-zhao Yu (Springer, 2023)
Abstract Focusing on local non-"Double First-Class" higher colleges in China, this study aims to explore the effects of classroom teaching, integration of industry and education, classroom involvement, interdisciplinary awareness and abilities, as well as teacher-student investment, on the increment of professional abilities of industrial design students, and explore effective teaching modes. Organizing questionnaire survey data, constructing a multiple linear regression model, and using the analytical method of sheaf coefficient found that student investment has the most decisive influence on low-order and high-order professional abilities, while other variables have their focuses. Teacher investment only has a direct impact on partial high-order professional capacities. The analysis of interactive effect regression models found that the interactive effects of significant influencing variables only mutually reinforce partial high-order professional abilities. The second-order factor structural equation modeling found that the professional capacities of industrial design have a strong endogeneity. The core mission of teachers is to promote "student-centered" teaching and integration of production and education and encourage students' investment to improve their professional ability. This study provides an empirical basis for optimizing and reconstructing the conceptual framework of low-order and high-order professional capacities in higher education.